Dyscalculia, Dysgraphia, and Left-Right Confusion from a Left Posterior Peri-Insular Infarct - S. Bhattacharyya; X. Cai; J. P. Klein (Behavioural Neurology)
The Gerstmann syndrome of dyscalculia, dysgraphia, left-right confusion, and finger agnosia is generally attributed to lesions near the angular gyrus of the dominant hemisphere. A 68-year-old right-handed woman presented with sudden difficulty completing a Sudoku grid and was found to have dyscalculia, dysgraphia, and left-right confusion. Magnetic resonance imaging (MRI) showed a focus of abnormal reduced diffusivity in the left posterior insula and temporoparietal operculum consistent with acute infarct. Gerstmann syndrome from an insular or peri-insular lesion has not been described in the literature previously. Pathological and functional imaging studies show connections between left posterior insular region and inferior parietal lobe. We postulate that the insula and operculum lesion disrupted key functional networks resulting in a pseudoparietal presentation.